If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -22 = 6x + 18 Reorder the terms: -22 + 2x = 6x + 18 Reorder the terms: -22 + 2x = 18 + 6x Solving -22 + 2x = 18 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -22 + 2x + -6x = 18 + 6x + -6x Combine like terms: 2x + -6x = -4x -22 + -4x = 18 + 6x + -6x Combine like terms: 6x + -6x = 0 -22 + -4x = 18 + 0 -22 + -4x = 18 Add '22' to each side of the equation. -22 + 22 + -4x = 18 + 22 Combine like terms: -22 + 22 = 0 0 + -4x = 18 + 22 -4x = 18 + 22 Combine like terms: 18 + 22 = 40 -4x = 40 Divide each side by '-4'. x = -10 Simplifying x = -10
| 4(x+n)=x | | 2x(x+3)-7=4x-6 | | Y=9y-72 | | 2(4x-1)+3(3-2x)= | | n+3=5n | | -132.6x(-53.78)= | | (2+c)=5(2+c)-6(2+c) | | -2(y)+2.82(-5)=24 | | 4a+3-a=7+2+a | | (2x+1)=(4x-3) | | 4(x-1)=6x | | y=-1000x^2+1100x-2.5 | | 4(6-6)=8 | | 4(x-4)=6x | | 3(-1-2)+6(2-4)= | | 9x-6=102 | | 5(x-2)=3(x-3) | | 5(y-4)/3=2y-5 | | 2(x+9)=24 | | 2.22m=4.4 | | -17=0.20n-20 | | -5(b+3)=-7b-1 | | x+25=-3(x-7) | | Y-8.1=20 | | 2w^2+15w+27=0 | | 7m-1=34 | | 6(3x+1)=-6x-18 | | 11h-7=-18 | | 2.5=1.3-r | | 2x-4+1= | | 3.3a=5.5b | | (25+x)(10+x)=1000 |